(3GdHjGf hGdJMUjd aj abg GdeGdcjgs - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s
(3ChdgG (B:s
(3ef SeGY GHf GdbGSe bGd SMfhf MOKfi EHf GdbGSe bGd SeYJ edckG bGd aef ESJCLQ YGedkG ef GdYeGd EeG fSLkG Ch NjGWkG Ch eG CTHg Pdc ef GdCYeGd s
(3BNQgG (B:s
(3aEPG bUO ai GdYed hLH Cf jQLY QH GdCQV Ydi GdYGed ef cSQ CQVg HbOQ eG bUO aiGdYed hHGddg GdJhajb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDdas
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs